Effect of Corporate Governance Implementation on Financial Performance - Mardiana, Nila; As’ari, Hasim (Research of Accounting and Governance, 2023)
This study examined the impact of independent commissioners, institutional ownership, and managerial ownership on the financial performance of mining companies listed on the Indonesia Stock Exchange from 2019 to 2022. Using a purposive sampling technique, 43 companies were selected. The findings revealed that independent commissioners had no significant effect on return on assets (ROA). Inadequate communication within larger boards hindered supervision, suggesting the importance of a well-coordinated independent board. The role of independent commissioners in monitoring management activities fell short of optimal performance, with companies meeting minimum requirements. Institutional ownership did not influence ROA, as institutional investors operated independently. Similarly, managerial ownership had no significant effect, indicating low ownership by managers in Indonesia. This implies that ownership information is not heavily considered in investment evaluations. In summary, the study highlights the limited impact of independent commissioners, institutional ownership, and managerial ownership on financial performance in the Indonesian mining sector. Effective communication and optimal governance structures are crucial for maximizing the benefits of independent boards, while ownership has minimal influence on financial performance in mining investments in Indonesia.